A merciful death - Elliot, Kendra (Elliot, Kendra. Mercy Kilpatrick novels, 2017)
FBI special agent Mercy Kilpatrick has been waiting her whole life for disaster to strike. A prepper since childhood, Mercy grew up living off the land - and off the grid - in rural Eagle's Nest, Oregon. Until a shocking tragedy tore her family apart and forced her to leave home. Now a predator known as the cave man is targeting the survivalists in her hometown, murdering them in their homes, stealing huge numbers of weapons, and creating federal suspicion of a possible domestic terrorism event. But the crime scene details are eerily familiar to an unsolved mystery from Mercy's past. Sent by the FBI to assist local law enforcement, Mercy returns to Eagle's Nest to face the family who shunned her while maintaining the facade of a law-abiding citizen. There, she meets police chief Truman Daly, whose uncle was the cave man's latest victim. He sees the survivalist side of her that she desperately tries to hide, but if she lets him get close enough to learn her secret, she might not survive the fallout.